Investigating The Students’ Challenges in Speaking English in English Club Program at an Islamic Boarding School in Jember - Siti Wardatun Jamilah (Faculty of Education, 2025)
Speaking is one of the most essential skills in English as a Foreign Language (EFL) learning, especially in environments that aim to produce communicatively competent individuals. In Islamic boarding schools (pesantren) that implement English Clubs as part of their language programs, students are expected to practice speaking in both formal and informal settings. However, many learners still struggle to speak English fluently and confidently. This research investigates the challenges students face in developing their speaking skills through English Club activities at a pesantren in Jember, East Java. Adopting a qualitative descriptive design with a deductive thematic analysis approach, this study collected data through semi structured interviews with three purposively selected participants who were actively involved in English Club programs. The participants were chosen based on consistent attendance, high speaking performance, and active classroom engagement. Thematic analysis was conducted using the framework by Braun and Clarke (2006), with themes aligned to pre existing theoretical categories of psychological, linguistic, and environmental barriers, as well as students’ perceptions of the program’s effectiveness. The analysis revealed four major themes: (1) Psychological Challenges, including anxiety, shyness, and fear of negative judgment; (2) Linguistic Challenges, such as limited vocabulary, weak grammar, and pronunciation uncertainty; (3) Environmental Challenges, like irregular scheduling, inconsistent policy enforcement, and peer discouragement; and (4) Perceived Effectiveness, where students acknowledged the positive impact of English Club activities like Daily Vocabulary Memorization (Muhadasah), Grammar and Pronuncation Class (Ta’limul Lughoh), and Public Speaking on their confidence and fluency. Despite the challenges, students viewed the English Club as a beneficial non formalplatform that supports speaking development, especially when activities are consistent, contextualized with Islamic values, and emotionally supportive. This study concludes that speaking challenges in pesantren based English Clubs are multidimensional and intertwined, influenced by internal psychological factors, language proficiency, and environmental support. It underscores the need for more structured, consistent, and culturally relevant speaking activities facilitated within emotionally safe environments. The study recommends that facilitators adopt student centered approaches, administrators strengthen policy enforcement, and future researchers explore the role of peer interaction and digital tools in enhancing EFL speaking fluency.
Reupload file repository 3 Februari 2026_Arif/Halima
Keywords: Investigating; Speaking English